Meaning in the Process Of Signification by the Advertisement of Hot Ones and LEGO Movie 2 - Andreas Dyka Terityus (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
This research aims to find meaning through the process of signification within the advertisement of Hot Ones and Lego Movie 2 by the use of verbal and visual expression. The focus of the analysis is the advertisement video. Using the process of signification, connotation, denotation and myth. These theories are used by the writer to analyze the meaning of the advertisement. Firstly, the writer finds meaning constructed in the advertisement. Then the writer discusses the findings. This research uses a descriptive qualitative method. Starting by compiling the data and transcribing the scenes into tables. The writer constructs meaning through verbal and visual data. Through the findings the writer found that meaning is created by the interaction of the characters. The index which was uncovered by using verbal and visual expression produces denotative and connotative meanings that are perceived by the audience as a myth.  Keywords: process of signification, myth, advertisement, LEGO, Hot Ones.